2004
DOI: 10.1021/ma0355352
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Lewis Acid Surfactant Combined Catalyst in Cationic Polymerization in Miniemulsion:  Apparent and Hidden Initiators

Abstract: A Lewis acid surfactant combined catalyst (LASC) was tentatively used in a cationic polymerization in miniemulsion of p-methoxystyrene (pMOS). In a first part, the initiating potential of trisdodecyl sulfate ytterbium (Yb(DS)3, 0.25H2O) was evidenced in the solution polymerization of pMOS initiated by the corresponding chlorinated adduct pMOS-HCl. Miniemulsion polymerizations of pMOS performed using the same initiating system gave rise to oligomers, but experimental conditions chosen could not evidence the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 19 publications
(49 reference statements)
4
68
1
Order By: Relevance
“…In the late 1990s, Sawamoto's team,12 followed by Ganachaud et al13 and D'Agosto et al,14 showed that rare earth triflates, dodecylbenzenesulfonic acid alone or with Yb(OTf) 3 induced cationic polymerization of p ‐alkoxystyrenes in aqueous suspension. However, these catalytic systems applied only for the polymerization of p ‐alkoxystyrenes and, therefore, were of little interest for industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s, Sawamoto's team,12 followed by Ganachaud et al13 and D'Agosto et al,14 showed that rare earth triflates, dodecylbenzenesulfonic acid alone or with Yb(OTf) 3 induced cationic polymerization of p ‐alkoxystyrenes in aqueous suspension. However, these catalytic systems applied only for the polymerization of p ‐alkoxystyrenes and, therefore, were of little interest for industry.…”
Section: Introductionmentioning
confidence: 99%
“…DAgosto et al [17] followed Kobayashis work to prepare LASC from ytterbium salts and the simple commercial surfactant sodium dodecyl sulfate.T he obtained complexes were,however,soluble neither in water nor in the monomer, and thus did not catalyze polymerization. Theu se of ytterbium complexed with bulky electrosteric anionic surfactants generated water-dispersible LASC.…”
mentioning
confidence: 99%
“…The number–average molecular weights of the synthesized polymers almost do not change with monomer conversion and slightly decrease while increasing the concentration of initiator (see Table 2). This indicates that the polymerization of CPD with 1/ B(C 6 F 5 ) 3 initiating system proceeds at the interface and that M n is controlled by interfacial polarity similarly to styrene23 or p ‐methoxystyrene13, 14 polymerization. The molecular weight distributions of the obtained polymers are typically somewhat higher than two as anticipated for irreversible transfer/termination reactions with water 13.…”
Section: Resultsmentioning
confidence: 91%